Ergonomía y las enfermedades laborales en los trabajadores del departamento de talento humano del Gobierno Autónomo Descentralizado del cantón Guaranda, provincia Bolívar, año 2024 - Guerrero Viscarra, Luis Fernando (2024)
The aim of the present research was to analyze the ergonomic factors and their incidence of occupational diseases of the staff of the Department of Human Talent of the Decentralized Autonomous Government of the Canton of Guaranda, year 2024. A methodology of a quantitative, descriptive type was carried out to carry it out. With a population of 8 professionals belonging to the Department of Human Talent of the institution under study. The technique used was the survey and the questionnaire tool. The results showed that there is an influence between ergonomics and occupational illnesses, considering that the risks identified as long-term sitting position, forced postures, use of data viewing screens, repetitive movements and manual manipulation have led to occupational diseases such as lumbar pain, fatigue and pain in shoulders and neck, frequent pain in the elbow and thighs. The need to establish preventive measures to prevent high levels of absence from work due to occupational diseases as well as high level of occupational stress was concluded.